A, The Effectiveness of Gym Ball Exercises Combined with the Back-and-Forth Child’s Pose in Reducing Low Back Pain Among Third-Trimester Pregnant Women - Siti Ni’amah; Siti Muawanah; Irfana Tri Wijayanti; Sri Hadi Sulistiyaningsih; Sholihah Gustavia Yolanda (Postgraduate, University of Mataram, 2026)
Back pain is one of the most common complaints experienced by pregnant women, particularly during the third trimester, as a result of physiological changes and the increased mechanical load on the spine. One non-pharmacological intervention that may help alleviate this condition is exercise using a gym ball combined with the Back-and-Forth Child’s Pose technique. This study aimed to determine the effect of gym ball exercises using the Back-and-Forth Child’s Pose method on reducing back pain among women in the third trimester of pregnancy. The study employed a pre-experimental design with a one-group pretest–posttest approach. Participants received the intervention in the form of Back-and-Forth Child’s Pose exercises using a gym ball twice daily for 10–15 minutes over a period of one week. Back pain intensity was measured before the intervention and again on the seventh day after the intervention using a standardized pain scale. The sample consisted of 15 third-trimester pregnant women who reported experiencing back pain. The results showed that before the intervention, 12 respondents (80%) experienced moderate pain and 3 respondents (20%) experienced mild pain. After the intervention, 10 respondents (66.6%) experienced mild pain, 3 respondents (20%) reported no pain, and only 2 respondents (13.4%) continued to experience moderate pain. Furthermore, the mean pain score decreased from 3.00 before the intervention to 1.96 after the intervention. Statistical analysis using the Wilcoxon Signed-Rank Test yielded a p-value of 0.000 (p < 0.05), indicating that gym ball exercises using the Back-and-Forth Child’s Pose method had a statistically significant effect on reducing back pain among women in the third trimester of pregnancy